2015
DOI: 10.1016/j.jmrt.2014.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Fluidized bed modeling applied to the analysis of processes: review and state of the art

Abstract: a b s t r a c tThe fluidized bed is a technology that involves multiple phases, allowing for efficient contact between them, therefore it is widely used in the chemical industry, metallurgy, oil and thermal power generation. In fluidized bed processes, the gas-solid interactions and chemical reactions generate a large number of variables to be handled, making the process very complex. Therefore, fluidized bed modeling and simulation is widely used to predict and analyze different processes, but it is possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Stirred tank bioreactors (STR) 18 , pneumatically agitated bioreactors (such as bubble column, and airlift column) 18 , membrane bioreactors (such as hollow fibres) 19 , fixed-bed bioreactors 17 , and fluidised-bed bioreactors 20 are the most typical reactors that have been used for encapsulation of both plant and mammalian cell culture. Of these systems, hollow fibres are the most studied bioreactors for the cultivation of mammalian cells, which have primarily been used clinically to treat liver failure as a bioartificial liver assist device 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Stirred tank bioreactors (STR) 18 , pneumatically agitated bioreactors (such as bubble column, and airlift column) 18 , membrane bioreactors (such as hollow fibres) 19 , fixed-bed bioreactors 17 , and fluidised-bed bioreactors 20 are the most typical reactors that have been used for encapsulation of both plant and mammalian cell culture. Of these systems, hollow fibres are the most studied bioreactors for the cultivation of mammalian cells, which have primarily been used clinically to treat liver failure as a bioartificial liver assist device 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, computational methods based on fundamental principles for resolving each particle–particle and fluid–particle interactions have allowed to explore many details of the underlying dynamics in fluidized beds. Using the computational fluid dynamics (CFD) techniques or lattice Boltzmann methods, the fluid hydrodynamics (obeying Navier–Stokes equations) is investigated on finer grids than the particles separations disclosing all forces exerted on the particles surface (drag), and deducing improved empirical correlations .…”
Section: Introductionmentioning
confidence: 99%
“…30 These correlations cannot all be used for the design of fluidised beds, since there is no model with universal applicability. 31 Comparisons of experimental U mf with theoretical predictions from correlations have been conducted. 32 The effect of palm kernel cake particle size was studied 33 and it was found that U mf increased with particle size.…”
Section: Introductionmentioning
confidence: 99%